A novel photoelectrochemical sensor for the detection of α-fetoprotein based on a mesoporous TiO2–CdS QD composite film. Issue 4 (7th January 2015) - Yang, Xiaoyan; Li, Jingyu; Fu, Junliang
Abstract : A label-free photoelectrochemical (PEC) immunosensor based on a CdS-modified mesoporous TiO2 film is reported to detect α-fetoprotein (AFP). The assay platform exhibits excellent selectivity and sensitivity. The detection limit of 0.02 ng mL −1 for AFP is obtained. Abstract : In this article, a label-free photoelectrochemical immunosensor based on a CdS-modified mesoporous TiO2 film has been developed. The CdS quantum dots could be deposited onto the mesoporous TiO2 film by electrochemical deposition, which could enhance the photocurrent intensity in the visible region. Employing specific binding of antigen–antibody, α-fetoprotein (AFP) could be captured on the surface of the modified electrode. Based on the steric hindrances, the photocurrent intensity decreased with the increase in AFP concentration. A linear response from 0.05 ng mL −1 to 20 ng mL −1 was obtained for AFP detection and the detection limit was 0.02 ng mL −1 . Moreover, the practical determination of AFP in human serum was also investigated.